2021
DOI: 10.1002/mp.14856
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of residual attention modules into two neural networks for low‐dose CT denoising

Abstract: Purpose The low‐dose computed tomography (CT) imaging can reduce the damage caused by x‐ray radiation to the human body. However, low‐dose CT images have a different degree of artifacts than conventional CT images, and their resolution is lower than that of conventional CT images, which can affect disease diagnosis by clinicians. Therefore, methods for noise‐level reduction and resolution improvement in low‐dose CT images have inevitably become a research hotspot in the field of low‐dose CT imaging. Methods In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 34 publications
2
12
0
Order By: Relevance
“…The optimization of the above objective function is equivalent to minimizing the Jensen-Shannon (JS) scatter between the real and synthetic data distributions [16]. WGAN introduces the Wasserstein distance/Earth mover's distance into the training by improving the loss function as…”
Section: Wganmentioning
confidence: 99%
“…The optimization of the above objective function is equivalent to minimizing the Jensen-Shannon (JS) scatter between the real and synthetic data distributions [16]. WGAN introduces the Wasserstein distance/Earth mover's distance into the training by improving the loss function as…”
Section: Wganmentioning
confidence: 99%
“…We first compare WGAN‐based denoising methods: WGAN‐VGG, 25 WGAN‐RAM, 23 and MAPNN 46 . The resultant images are shown in Figure 4e–g.…”
Section: Methodsmentioning
confidence: 99%
“…In the following experimental studies, we presented the experimental setup and demonstrated the performance of the proposed DADN network model by showing details of the image datasets used in the studies and the test‐resultant images. Five neural network models, RED‐CNN, 22 ED‐CNN, 24 WGAN‐VGG, 25 WGAN‐RAM, 23 and MAPNN, 46 were used in comparison with the proposed DADN.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The US National Academy of Sciences defined low doses of radiation as those up to ~100 mSv (45). At present, low-dose CT imaging methods can be mainly divided into three categories: image postprocessing methods, iterative reconstruction methods, or projection domain filtering methods (46).…”
Section: Ct Use and Low-dose Radiationmentioning
confidence: 99%